Results of the Genetic Counselor SARS‐CoV‐2 Impact Survey from the National Society of Genetic Counselors: Progress and penalty during the COVID‐19 pandemic. Issue 4 (26th July 2021) - Pan, Vivian; Doerr, Megan; Hoell, Christin; Ryan, Lauren; Erwin, Deanna J.; Hooker, Gillian; Haverty, Carrie; ,
Abstract: The Genetic Counselor SARS‐CoV‐2 Impact Survey (GCSIS) describes the impact of the pandemic on genetic counselors and genetic counseling services. With this information, the National Society of Genetic Counselors (NSGC) can better: (1) support advocacy and access efforts for genetic counseling services at both federal‐ and state‐level; (2) promote effective billing and reimbursement for genetic counseling services provided via telemedicine; and (3) make decisions about how to best support genetic counselors. The survey was hosted on a novel data collection and analysis platform from LunaDNA and was open to all genetic counselors ( n = 5, 531 based on professional society membership). Survey response rate was approximately 3.8% ( n = 212/5, 531), with a demographic distribution broadly representative of the North American genetic counseling field. Genetic counselors remained largely employed, providing genetic counseling services throughout the pandemic, although almost one in five respondents (17%, n = 35/211) reported experiencing some degree of pandemic‐related financial hardship. Nearly all respondents (90%, n = 104/115) transitioned, at least in part, to remote work settings, with about half (47%. n = 88/189) reporting restrictions in the care they were able to provide. These shifts came at a cost: existing gaps in Medicare status for genetic counselors and attendant reimbursement concerns led to uncertainty about whether genetic counselors' work will be reimbursed. Outside of work, caregiving responsibilities increased for 34% ( n = 74/212) of respondents. The results of the GCSIS amplify the importance of federal‐ and state‐level advocacy efforts for genetic counselors and their employers. They also highlight the impact of broader cultural intransigence on our majority‐female profession. During the pandemic, genetic counselors continued to provide care, but without consistent financial support or expectation of reimbursement. The ability to attract and retain talented professionals to the genetic counseling field will hinge on the success of continued advocacy efforts.